Effects of irradiation time on the structural, elastic, and optical properties of hexagonal (wurtzite) zinc oxide nanoparticle synthesised via microwave-assisted hydrothermal route - Shitu, Ibrahim Garba; Katibi, Kamil Kayode; Muhammad, Aminu; Chiromawa, Idris Muhammad; Tafida, Rabiu Abubakar; Amusa, Abiodun Abdulhameed; Babani, Suleiman (Springer, 2023)
Zinc oxide (ZnO) is a vital nanomaterial highly valued in electronics and optoelectronics due to its remarkable multifunctional properties. This study prepared ZnO nanoparticles using a simple hydrothermal microwave process. The influence of irradiation time on the structural, elastic and optical properties of the ZnO nanoparticles was investigated. X-ray diffraction (XRD) analysis confirmed the hexagonal (wurtzite) structure of the ZnO nanoparticles. In addition, various XRD profile analysis techniques were used in this study, including Scherer method, strain size plot method, Halder–Wagner method, Monshi–Scherer method, and Williamson–Hall method consisting of a uniform deformation model, a uniform stress density model and a uniform deformation energy density model. The estimated mean crystallite size was found to be at 43.53–56.08 nm. Furthermore, atomic force microscopy and transmission electron microscopy were used to investigate the average particle size of the ZnO nanoparticles at different irradiation times. The results were consistent with the mean crystallite size calculated using the X-ray diffraction peak profile analysis techniques. Furthermore, a decrease in the energy band gap estimated by diffuse reflectance spectroscopy was observed, transitioning from 3.32s to 3.29 eV with increasing irradiation time. This observation was confirmed by the distinct and unique ultraviolet photoluminescence emission peaks of the synthesized ZnO nanoparticles, supporting the results of the diffuse reflectance analysis. Based on the presented results, it can be concluded that the X-ray diffraction peak profiling technique is a practical approach for determining the average crystallite size of ZnO nanoparticles prepared using the microwave hydrothermal technique and that it can be used for size-dependent applications.